2017
DOI: 10.12688/f1000research.11027.1
|View full text |Cite
|
Sign up to set email alerts
|

SNP-SNP interactions as risk factors for aggressive prostate cancer

Abstract: Prostate cancer (PCa) is one of the most significant male health concerns worldwide. Single nucleotide polymorphisms (SNPs) are becoming increasingly strong candidate biomarkers for identifying susceptibility to PCa. We identified a number of SNPs reported in genome-wide association analyses (GWAS) as risk factors for aggressive PCa in various European populations, and then defined SNP-SNP interactions, using PLINK software, with nucleic acid samples from a New Zealand cohort. We used this approach to find a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Lumbar disc herniation is determined by multiple genetic and environmental interactions. Single nucleotide polymorphisms (SNPs) are increasingly becoming candidate biomarkers for determining susceptibility to complex diseases (Vaidyanathan et al, 2017). A single SNP in a single gene may not be enough to affect overall cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc herniation is determined by multiple genetic and environmental interactions. Single nucleotide polymorphisms (SNPs) are increasingly becoming candidate biomarkers for determining susceptibility to complex diseases (Vaidyanathan et al, 2017). A single SNP in a single gene may not be enough to affect overall cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that mutations and GVs involved in cell expansion interact in an organized manner in prostate cancer, implying that GVs can work with mutations as "tumor co-suppressors" or "co-oncogenes" [66,67]. Aggressive forms of prostate cancer, for instance, have been found in individuals with SNPs-SNPs communication with variants such as MMP16, CSF1, EGFR, and more [68,69]. Besides, the consequences are even more complex to predict because GVs affect risk at the epigenetic level [70] and are affected by additional environmental factors [71].…”
Section: Prostate Cancer (Pc)mentioning
confidence: 99%